Method for preparing nano calcium carbonate by self-switching type microemulsion method
Through the self-switching microemulsion method, calcium extraction is used to extract calcium with carbon dioxide and carbonization, the preparation of nano-calcium carbonate and raw material recycling are achieved, and the problems of high material loss and high cost in the prior art are solved, and the nano-calcium carbonate particle size is also solved. Even.
Patent Information
- Application Number
- CN202411417510.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-14
AI Technical Summary
The existing microemulsion method for preparing nano calcium carbonate has problems of high material loss and high cost, and it is difficult to realize the recycling of raw materials.
The self-switching microemulsion method is used to extract calcium through calcium carbide slag, mix oil-phase solution, surfactant and calcium-containing aqueous solution, and add carbon dioxide to carbonize to achieve the preparation of nano-calcium carbonate, and recycle the aqueous phase and the oil phase. Solution, reduces material loss and reduces cost.
It effectively reduces material loss during the preparation of nano calcium carbonate, reduces costs, and the prepared nano calcium carbonate particle size is uniform.
Smart Images

Figure CN119306240A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano calcium carbonate, and in particular relates to a method for preparing nano calcium carbonate by a self-switching microemulsion method. Background Art
[0002] Calcium carbide slag is the waste residue with calcium hydroxide as the main component after acetylene gas is obtained by hydrolysis of calcium carbide. Calcium carbide slag is a calcium-containing solid waste. At present, most of the treatment of calcium carbide slag is to use calcium carbide slag to replace limestone to make cement and produce quicklime as calcium carbide raw material. However, there are problems of insufficient utilization and low added value. The use of calcium carbide slag to prepare nano calcium carbonate can effectively improve the resource utilization rate and added value of solid waste calcium carbide slag.
[0003] Nano calcium carbonate, also known as ultrafine calcium carbonate, is mainly used in high-end plastic products. The commonly used preparation method of nano calcium carbonate is the microemulsion method, which can control the nucleation and growth of grains in a smaller area by controlling the reaction conditions, thereby obtaining nano-scale calcium carbonate particles. However, the existing microemulsion method for preparing nano calcium carbonate has the following problems: nano calcium carbonate is directly obtained after the microemulsion is demulsified, but the residual solution cannot be recycled, resulting in a waste of raw materials, making the preparation of nano calcium carbonate have the problems of high raw material loss and high cost. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a method for preparing nano calcium carbonate by a self-switching microemulsion method, which solves the problems of high material loss and high cost in the preparation process of nano calcium carbonate; and the prepared nano calcium carbonate has uniform particle size.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A method for preparing nano-calcium carbonate by a self-switching microemulsion method, the method for preparing nano-calcium carbonate by a self-switching microemulsion method comprising the following steps:
[0007] Step 1: Method for extracting calcium from carbide slag
[0008] The method for extracting calcium from carbide slag comprises: leaching the carbide slag with a leaching agent to obtain a leaching mixed solution; further separating the leaching mixed solution to obtain a calcium-containing aqueous phase solution;
[0009] Step 2: Preparation method of self-switching microemulsion
[0010] The microemulsion preparation method comprises mixing an oil phase solution, a surfactant, a booster surfactant and the calcium-containing aqueous phase solution in step 1 to prepare a self-switching microemulsion; the oil phase solution comprises n-hexane and a self-switching compound;
[0011] Step 3: Carbon dioxide carbonization method
[0012] Passing carbon dioxide into the microemulsion prepared in step 2 for carbonization and demulsification to obtain a demulsified solution;
[0013] Step 4: Extractant and microemulsion recycling method
[0014] The demulsified solution obtained in step 3 is subjected to water-oil phase separation to obtain a water-phase demulsified solution and an oil-phase solution;
[0015] The aqueous phase demulsified solution is separated to obtain nano calcium carbonate and an aqueous phase, and the aqueous phase is circulated as an extractant; the oil phase solution is recycled.
[0016] It is further defined that in step one, the leaching agent is an ammonium chloride solution, the mass concentration of the ammonium chloride solution is 10%, and the solid-liquid mass ratio of carbide slag to the ammonium chloride solution is (1:5) to (1:8).
[0017] It is further defined that in the step 1, when the ammonium chloride solution is used to leaching carbide slag, the pH of the leaching agent is 10 to 12, and the leaching time is greater than or equal to 25 minutes.
[0018] It is further defined that in step 2, the mass ratio of the surfactant, the self-switching compound, n-hexane, the co-surfactant and the calcium-containing aqueous solution is 1:1.5:4:6:1.25.
[0019] It is further defined that in step 2, the self-switching compound is a long-chain alkyl compound whose head group is a guanidine group, an amidine group or an amine group; the surfactant is sodium dodecylbenzene sulfonate, and the co-surfactant is n-butanol.
[0020] It is further defined that in step 2, the self-switching compound is N′-hexadecyl-N,N-dimethylethylamidine, N′-hexadecyl-N,N-dimethylethylguanidine or N′-hexadecyl-N,N-dimethylethylamine.
[0021] It is further defined that in step three, the carbonization equipment is a microbubble generator, and the carbonization process conditions are: the carbonization time is greater than or equal to 20 minutes, the rotation speed is greater than 300 rpm, and the carbon dioxide flow rate is 200 ml / min.
[0022] It is further defined that in step three, the carbonization temperature is 20°C to 25°C.
[0023] It is further defined that the step 1 further includes adding a crystal form control agent to the calcium-containing aqueous solution, and the mass ratio of the crystal form control agent to the calcium-containing aqueous solution is 0.5%-1%.
[0024] It is further defined that in the step three, the oil phase solution is heated to 70° C., carbon dioxide is removed, and the solution is returned to the step two to form a new liquid system with the fresh calcium-containing aqueous phase solution, which is mixed and stirred to form a new self-switching microemulsion; ammonium chloride is first added to the aqueous phase and then circulated again as a leaching agent.
[0025] Compared with the prior art, the present invention provides a method for preparing nano calcium carbonate by a self-switching microemulsion method, which has the following beneficial effects:
[0026] The invention mixes an oil phase solution, a surfactant, a booster surfactant and the calcium-containing aqueous phase solution in step one, and since the oil phase solution includes n-hexane and a self-switching compound, a self-switching microemulsion is formed; then carbon dioxide is introduced into the self-switching microemulsion to form a carbon dioxide self-switching microemulsion, and then nano-calcium carbonate is prepared; the carbon dioxide first promotes the nano-calcium carbonate in the self-switching microemulsion, and after the reaction is complete, the carbon dioxide changes the pH of the self-switching microemulsion, thereby achieving demulsification and separation of the nano-calcium carbonate, and then the demulsified organic phase and the new calcium-containing aqueous phase solution form a new cycle to continue to prepare the self-switching microemulsion, and the separated aqueous phase is used as an extractant to circulate continuously, thereby reducing material loss in the process of preparing the nano-calcium carbonate and reducing the preparation cost of the nano-calcium carbonate. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a process flow chart of the nano calcium carbonate prepared by the present invention;
[0028] Figure 2 This is a scanning electron microscope image of the nano calcium carbonate prepared by the present invention. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] See also Figure 1 The present invention provides a method for preparing nano calcium carbonate by a self-switching microemulsion method, comprising the following steps:
[0031] Step 1: Method for extracting calcium from carbide slag
[0032] The method for extracting calcium from carbide slag comprises: leaching the carbide slag with a leaching agent to obtain a leaching mixed solution; and further separating the leaching mixed solution to obtain a calcium-containing aqueous phase solution.
[0033] In step 1 of the present invention, the leaching agent is selected as ammonium chloride solution, the mass concentration of the ammonium chloride solution is 10%, and the solid-liquid mass ratio of carbide slag to the ammonium chloride solution is (1:5) to (1:8).
[0034] In the present invention, the solid-liquid mass ratio is 1:5, 1:6, 1:7 or 1:8.
[0035] In step 1 of the present invention, when the ammonium chloride solution is used to leaching carbide slag, the pH of the leaching agent is 10-12, and the leaching time is greater than or equal to 25 minutes.
[0036] In step 1 of the present invention, the method further comprises adding a crystal form control agent to the calcium-containing aqueous phase solution, wherein the mass ratio of the crystal form control agent to the calcium-containing aqueous phase solution is 0.5%-1%.
[0037] In the present invention, the mass ratio of the crystal form controlling agent to the calcium-containing aqueous solution is 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%.
[0038] Preferably, the crystal form controlling agent is sucrose, and other crystal form controlling agents having the same or similar properties and functions as sucrose may also be selected.
[0039] Step 2: Preparation method of self-switching microemulsion
[0040] The microemulsion preparation method comprises mixing an oil phase solution, a surfactant, a booster surfactant and the calcium-containing aqueous phase solution in step one to prepare a self-switching microemulsion; the oil phase solution comprises n-hexane and a self-switching compound.
[0041] In step 2 of the present invention, the mass ratio of the surfactant, the self-switching compound, n-hexane, the co-surfactant and the calcium-containing aqueous solution is 1:1.5:4:6:1.25.
[0042] In step 2 of the present invention, the self-switching compound is a long-chain alkyl compound whose head group is a guanidine group, an amidine group or an amine group; the surfactant is sodium dodecylbenzene sulfonate, and the co-surfactant is n-butanol.
[0043] In step 2 of the present invention, the self-switching compound is N′-hexadecyl-N, N-dimethylethylamidine, N′-hexadecyl-N, N-dimethylethylguanidine or N′-hexadecyl-N, N-dimethylethylamine.
[0044] Step 3: Carbon dioxide carbonization method
[0045] Carbon dioxide is introduced into the microemulsion prepared in step 2 for carbonization and demulsification to obtain a demulsified solution.
[0046] In step three of the present invention, a microbubble generator is selected as the carbonization equipment, and the carbonization process conditions are: the carbonization time is greater than or equal to 20 minutes, the rotation speed is greater than 300 rpm, and the carbon dioxide flow rate is 200 ml / min.
[0047] In step three of the present invention, the carbonization temperature is 20°C to 25°C.
[0048] Step 4: Extractant and microemulsion recycling method
[0049] The demulsified solution obtained in step 3 is subjected to water-oil phase separation to obtain a water-phase demulsified solution and an oil-phase solution;
[0050] The aqueous phase demulsified solution is separated to obtain nano calcium carbonate and an aqueous phase, and the aqueous phase is circulated as an extractant; the oil phase solution is recycled.
[0051] In step 4 of the present invention, the oil phase solution is heated to 70° C., carbon dioxide is removed, and the oil phase solution is returned to step 2 to form a new liquid system with a fresh calcium-containing aqueous phase solution, and mixed and stirred to form a new self-switching microemulsion; ammonium chloride is first added to the aqueous phase and then circulated again as a leaching agent.
[0052] The preparation method of the present invention is described in detail below with reference to specific examples.
[0053] It should be noted that, unless otherwise specified, the chemicals, reagents, etc. used in the following examples are conventional commercially available products.
[0054] It should be noted that, unless otherwise specified, the chemical operations used in the following examples are all conventional operating steps in the art.
[0055] 1. Optimization of carbide slag leaching conditions
[0056] Before specific implementation, the leaching conditions of the method for extracting calcium by leaching carbide slag are optimized, as follows.
[0057] 1.1, Based on calcium content NH 4 + / Ca 2+ Stoichiometric ratio
[0058] The calcium source in the raw material is carbide slag, which is a by-product of acetylene production from carbide, and its main component is Ca(OH) 2 The leaching agent is ammonium chloride solution, which can effectively leach calcium ions from carbide slag and regenerate it for leaching after carbonization to achieve recycling.
[0059] The carbide slag was mixed with ammonium chloride solution according to the NH4Cl2 content. 4 + / Ca 2+The stoichiometric ratios were 0.9 to 1.2, respectively, and the mixtures were fed into the reactor. The leaching time was 2 hours. The leaching rate results are shown in Table 1.
[0060] Table 1 Different NH 4 + / Ca 2+ Stoichiometric extraction results
[0061] Stoichiometric ratio 0.9 1 1.1 1.2 Extraction rate 90% 91% 93% 92%
[0062] It can be seen from Table 1 that with the increase in the amount of leaching agent, the calcium leaching rate shows a trend of first increasing and then decreasing. 4 + / Ca 2+ Within the range of stoichiometric ratio, the calcium extraction rate is above 90%. In the method of extracting calcium from carbide slag with ammonium chloride solution, the NH 4 + / Ca 2+ The stoichiometric ratio process conditions are: 0.9 to 1.2. Preferably, based on the calcium content NH 4 + / Ca 2+ The stoichiometric ratio is 1.1, at which the maximum leaching rate is 93%.
[0063] 1.2. Solid-liquid ratio of carbide slag and ammonium chloride solution
[0064] The carbide slag and ammonium chloride solution were fed into the reactor according to the solid-liquid mass ratio listed in Table 2. The leaching time was 2 hours. The leaching rate results are listed in Table 2.
[0065] Table 2 Leaching rate at different solid-liquid ratios
[0066] Solid-liquid ratio 1:5 1:6 1:8 1:13 Extraction rate 94% 98% 96% 95%
[0067] As can be seen from Table 2, as the solid-liquid ratio increases, the leaching first increases and then decreases. When the solid-liquid ratio is 1:13, the leaching rate effect is not much different from that of 1:5. Therefore, in the leaching of calcium by ammonium chloride solution, the process conditions of the solid-liquid mass ratio of carbide slag to ammonium chloride solution range from 1:5 to 1:8. Preferably, the solid-liquid mass ratio of carbide slag to ammonium chloride solution is 1:6, at which time the leaching rate is as high as 98%.
[0068] Preferably, in the method for preparing calcium carbonate using carbide slag as a calcium source, the leaching method conditions are: the concentration of the leaching agent ammonium chloride is 10% ammonium chloride, and the solid-liquid ratio of the carbide slag to the ammonium chloride solution is 1:6.
[0069] 1.3. pH of the extractant
[0070] When carbide slag is leached with ammonium chloride solution, the pH of the leaching agent is in the range of 10 to 12. It should be noted that the technical effect of leaching with a pH of 10 to 12 is that carbide slag contains a large amount of calcium resources, with a content of more than 91% on a dry basis as CaO, and contains a small amount of silicon and aluminum, with contents of about 3.56% and 1.65% respectively, and trace magnesium and iron contents of 0.16% and 0.65% respectively. The pH selected as 10 to 12 can effectively avoid the leaching of impurity ions and ensure the stability of the ammonium chloride solution.
[0071] 1.4. Extraction time
[0072] The leaching time of calcium element by ammonium chloride solution is within 15-40 minutes, and the leaching effect is listed in Table 3.
[0073] Table 3 Leaching rate at different leaching times
[0074] Extraction time 15 20 25 30 40 Extraction rate 88% 89% 90% 91% 87%
[0075] It can be seen from Table 3 that as the leaching time increases, the leaching rate decreases instead of increases, and the leaching time should be guaranteed to be greater than or equal to 25 minutes. Preferably, the leaching time process condition is 30 minutes, at which time the leaching rate is as high as 91%.
[0076] In summary, as a preferred embodiment, the conditions for extracting calcium from carbide slag by leaching ammonium chloride solution are as follows: carbide slag is used as the calcium source, the mass fraction of ammonium chloride in the leaching agent ammonium chloride solution is 10%, carbide slag is the solid phase, the leaching agent is the liquid phase, the solid-liquid mass ratio is 1:6, the leaching time is 30 minutes, and the pH value of the leaching agent solution is 10 to 12. Under this leaching condition, the calcium leaching rate is stable at more than 90%, and its average value is ≥92%; the calcium ion concentration in the obtained calcium ion solution is about 1.5 mol / L, the pH value is 10 to 12, the impurity ion content is low, and impurities such as Fe, Mg, and Al are not detected by titration test.
[0077] Example 1
[0078] The method for preparing nano calcium carbonate by a self-switching microemulsion method provided in this embodiment comprises the following steps:
[0079] Step 1: Method for extracting calcium from carbide slag
[0080] In this embodiment, carbide slag is used as the calcium source, the mass fraction of ammonium chloride in the leaching agent ammonium chloride solution is 10%, the carbide slag is the solid phase, the leaching agent is the liquid phase, the solid-liquid mass ratio is 1:6, the leaching time is 30 minutes, and the pH value of the leaching agent solution is 10-12.
[0081] In this embodiment, carbide slag is leached according to the above conditions to obtain a leaching mixture; the leaching mixture is further separated to obtain a calcium-containing aqueous phase solution.
[0082] Step 2: Preparation of self-switching microemulsion
[0083] The addition of a crystal form control agent can effectively control the morphology and dispersibility of nano-calcium carbonate. Sucrose is preferably used as the crystal form control agent. The crystal form control agent is added to the calcium-containing aqueous phase solution, and the mass ratio of sucrose to the calcium-containing aqueous solution in the leaching solution is 0.8%.
[0084] In this embodiment, the method for preparing the self-switching microemulsion is to mix the oil phase solution, the surfactant, the auxiliary surfactant and the calcium-containing aqueous phase solution in step one to prepare the self-switching microemulsion; the oil phase solution includes n-hexane and the self-switching compound.
[0085] Specifically, a surfactant, a self-switching compound, n-hexane, a co-surfactant and a calcium-containing aqueous phase solution containing a crystal form control agent were mixed in a mass ratio of 1:1.5:4:6:1.25, and stirred to prepare a self-switching microemulsion. The conductivity of the self-switching microemulsion was measured to be: 30 μS·cm -1。
[0086] In this embodiment, the self-switching compound is N'-hexadecyl-N,N-dimethylethylamidine, the co-surfactant is n-butanol, and the surfactant is sodium dodecylbenzenesulfonate.
[0087] Step 3: Carbon dioxide carbonization method
[0088] The carbonization equipment uses a microbubble generator, which can effectively generate micro-nano bubbles. The carbonization time is 20 minutes, the rotation speed is greater than 300 rpm, the carbon dioxide flow rate is 200 ml / min, and the external water bath controls the reaction temperature at the corresponding temperature of 10°C to 15°C.
[0089] Carbon dioxide was introduced into the self-switching microemulsion at a rate of 200 ml / min for 20 minutes, and its conductivity was measured as follows: conductivity 220 μS·cm -1 As the pH of the solution changes, the microemulsion breaks to obtain a demulsified solution.
[0090] Step 4: Recycling of leaching agent microemulsion
[0091] The demulsified solution is phase-separated to obtain an aqueous phase solution and an oil phase solution; further, nano calcium carbonate and an aqueous phase are separated from the aqueous phase solution, and an appropriate amount of ammonium chloride is added to the aqueous phase to form a leaching agent, which is circulated again to prepare a calcium-containing aqueous phase solution; the oil phase solution is further heated to 70° C., carbon dioxide is removed from the liquid system, and then a new calcium-containing aqueous solution is added to form a new liquid system, and the conductivity of the new liquid system is measured to be: conductivity 40 μS·cm -1 , mixed and stirred to form a new self-switching microemulsion.
[0092] Embodiment 2 to Embodiment 6
[0093] Different from Example 1, the temperature of carbonization of carbon dioxide is different. For specific temperature settings, see Table 4.
[0094] The yield and average particle size of the nano calcium carbonate prepared above were calculated, and the results are listed in Table 4.
[0095] Table 4 Yield and average particle size of nano calcium carbonate at different carbonization temperatures
[0096] Serial number Temperature(℃) Calcium carbonate yield (%) Average particle size of calcium carbonate (nm) Example 1 10-15 99 32 Example 2 15-20 98 28 Example 3 20-25 99 43 Example 4 25-30 98 65 Example 5 30-35 98 92 Example 6 35-40 99 106
[0097] As can be seen from Table 4, as the temperature increases, the yield of nano calcium carbonate does not change much, basically fluctuating between 98% and 99%, but as the temperature increases, the particle size of nano calcium carbonate almost increases. Considering comprehensively, the carbonization equipment uses a micro bubble generator, which can effectively generate micro-nano bubbles, the carbonization time is greater than or equal to 20 minutes, the rotation speed is greater than 300 rpm, the carbon dioxide flow rate is 200 ml / min, and the external water bath controls the reaction temperature at a corresponding temperature of 20°C to 25°C. The morphology of the nano calcium carbonate obtained at this time is shown in Figure 2 .
[0098] In summary, the present invention extracts a calcium-containing aqueous solution from carbide slag, prepares a self-switching microemulsion by adding a self-switching compound, n-hexane, a surfactant and a co-surfactant, further carbonizes by adding carbon dioxide, utilizes the carbon dioxide to first promote nano-calcium carbonate in the self-switching microemulsion, and after the reaction is complete, the carbon dioxide changes the pH of the self-switching microemulsion, realizes demulsification and separation of nano-calcium carbonate, and realizes the recycling of oil phase and water phase while preparing nano-calcium carbonate, thereby solving the problems of high material loss and high cost and technology in the preparation process of nano-calcium carbonate; and the prepared nano-calcium carbonate has uniform particle size.
[0099] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing nano calcium carbonate by a self-switching microemulsion method, characterized in that: The method for preparing nano calcium carbonate by the self-switching microemulsion method comprises the following steps: Step 1: Method for extracting calcium from carbide slag The method for extracting calcium from carbide slag comprises: leaching the carbide slag with a leaching agent to obtain a leaching mixed solution; further separating the leaching mixed solution to obtain a calcium-containing aqueous phase solution; Step 2: Preparation method of self-switching microemulsion The microemulsion preparation method comprises mixing an oil phase solution, a surfactant, a booster surfactant and the calcium-containing aqueous phase solution in step 1 to prepare a self-switching microemulsion; the oil phase solution comprises n-hexane and a self-switching compound; Step 3: Carbon dioxide carbonization method Passing carbon dioxide into the microemulsion prepared in step 2 for carbonization and demulsification to obtain a demulsified solution; Step 4: Extractant and microemulsion recycling method The demulsified solution obtained in step 3 is subjected to water-oil phase separation to obtain a water-phase demulsified solution and an oil-phase solution; The aqueous phase demulsified solution is separated to obtain nano calcium carbonate and an aqueous phase, and the aqueous phase is circulated as an extractant; the oil phase solution is recycled.
2. The method for preparing nano calcium carbonate by the self-switching microemulsion method according to claim 1, characterized in that: In the step 1, the leaching agent is selected as ammonium chloride solution, the mass concentration of the ammonium chloride solution is 10%, and the solid-liquid mass ratio of carbide slag to the ammonium chloride solution is (1:5) to (1:8).
3. The method for preparing nano calcium carbonate by the self-switching microemulsion method according to claim 2, characterized in that: In the step 1, when the ammonium chloride solution is used to leaching carbide slag, the pH of the leaching agent is 10-12, and the leaching time is greater than or equal to 25 minutes.
4. The method for preparing nano calcium carbonate by the self-switching microemulsion method according to claim 6, characterized in that: In the step 2, the mass ratio of the surfactant, the self-switching compound, n-hexane, the co-surfactant and the calcium-containing aqueous solution is 1:1.5:4:6:1.
25.
5. The method for preparing nano calcium carbonate by the self-switching microemulsion method according to claim 1, characterized in that: In the step 2, the self-switching compound is a long-chain alkyl compound whose head group is a guanidine group, an amidine group or an amine group; the surfactant is sodium dodecylbenzene sulfonate, and the co-surfactant is n-butanol.
6. The method for preparing nano calcium carbonate by the self-switching microemulsion method according to claim 4, characterized in that: In the step 2, the self-switching compound is N′-hexadecyl-N, N-dimethylethylamidine, N′-hexadecyl-N, N-dimethylethylguanidine or N′-hexadecyl-N, N-dimethylethylamine.
7. The method for preparing nano calcium carbonate by the self-switching microemulsion method according to claim 1, characterized in that: In the step 3, the carbonization equipment is a microbubble generator, and the carbonization process conditions are: the carbonization time is greater than or equal to 20 minutes, the rotation speed is greater than 300 rpm, and the carbon dioxide flow rate is 200 ml / min.
8. The method for preparing nano calcium carbonate by the self-switching microemulsion method according to claim 1, characterized in that: In the step 3, the carbonization temperature is 20°C to 25°C.
9. The method for preparing nano calcium carbonate by the self-switching microemulsion method according to claim 1, characterized in that: The step 1 also includes adding a crystal form control agent to the calcium-containing aqueous solution, wherein the mass ratio of the crystal form control agent to the calcium-containing aqueous solution is 0.5%-1%.
10. The method for preparing nano-calcium carbonate by a self-switching microemulsion method according to any one of claims 1 to 9, characterized in that: In the step 3, the oil phase solution is heated to 70° C., carbon dioxide is removed, and the solution is returned to the step 2 to form a new liquid system with the fresh calcium-containing aqueous phase solution, and mixed and stirred to form a new self-switching microemulsion; ammonium chloride is first added to the aqueous phase and then circulated again as a leaching agent.
Citation Information
Cited By
Process of high-surface-activity nanoscale calcium hydroxide for lubricating oil
CN120423587A
Graphene oily slurry as well as preparation method and application thereof
CN120964788A